Gastroenteritis-Overview - DR.SACHIN B.INGLE; DR.CHITRA R. HINGE (INGLE) (International Journal of Pharma and Bio Sciences, 2012)
Gastroenteritis (also known as gastric flu, stomach flu, gastro and stomach virus, although unrelated to influenza) is marked by inflammation of the gastrointestinal tract involving both the stomach and small intestine resulting in diarrhea, vomiting and abdominal cramps. The majority of cases in children globally are caused by rotavirus, while in adults norovirus is more common, at least in the United States. Less common causes include bacteria or their toxins, and parasites. Transmission may occur due to improperly prepared foods, contaminated water or close contact with those who are infectious. The foundation of management is adequate hydration. For mild or moderate cases this can typically be achieved via oral rehydration solution. For more severe cases intravenous fluids may be needed. Gastroenteritis primarily affects children and those in the developing world.